Al-Ghazali’s Metaphysical Philosophy of Spiritualism In The Book Of Ihya ‘Ulumuddin - Supriyanto, Supriyanto (Green Publisher Indonesia, 2022)
This article tries to explore al-Ghazali’s views regarding philosophy—particularly metaphysical philosophy, and its influence on the establishment of al-Ghazali’s teachings as stated in the book ihya ʻulumuddin. The method used in this research is descriptive-qualitative method, and is included in the literature research (library research). The process of collecting data in this study is to make observations, in the sense of tracking various references that have relevance to the focus of the study, both from books, articles, and so on that function to support these data. The data analysis technique used in this research is the method of content analysis. In this analysis, the process of selecting, comparing, combining, and sorting information obtained from related data sources will be carried out to obtain valid inferences. From the studies conducted, it can be seen that: 1) Regarding the existence of God, al-Ghazali rejected the philosophical ideas of atheism (ad-dahriyun) and naturalism (al-thabi’iyun) as a whole. 2) al-Ghazali accepted the philosophical thought of divinity (ilahiyun), in several respects as a whole—for example logic, physics, mathematics, etc., and in terms of metaphysics, al-Ghazali accepted with certain conditions—in accordance with the texts of the Qur’an and hadith. 3) Al-Ghazali’s partial disagreement with metaphysical philosophers, such as Ibn Sina and al-Farabi is because both of them have collided with the principal “norms” in religion. 4) His refusal formed al-Ghazali’s thought structure which is presented in several of his works—including in the Book of ihya ʻulumuddin.